The use of feedback in teaching undergraduate dental students: feedback sandwich or Ask-Tell-Ask model? - Galvin Sim Siang Lin; Wen Wu Tan; Hasnah Hashim; Chan Choong Foong (BMC, 2023)
Abstract Background Feedback is regarded as a key component of formative assessment and one of the elements with the greatest impact on students' academic learning. The present study aimed to evaluate and compare students' perceptions of the use of two feedback models, namely feedback sandwich and Ask-Tell-Ask (ATA), in teaching dental materials science courses. Methods All undergraduate second-year dental students were invited to participate in the dental materials science practical session and were randomly allocated into two groups: Group 1 (feedback) sandwich and Group 2 (ATA). The session began with the teacher giving a short briefing on the commonly used dental materials, followed by a short demonstration of the manipulation of those materials. Students were then allowed to mix and manipulate the materials, and teachers provided feedback accordingly. At the end of the session, 16 close-ended (five-point Likert scales) and an open-ended questionnaire were distributed to students to evaluate their perceptions of the feedback given. Internal reliability of the questionnaire items was evaluated using Cronbach's alpha. Mean feedback scores were analysed using an independent t-test with ANCOVA for controlling gender and ethnicity. Thematic analysis was used to code the qualitative data. Results Sixty-nine students participated in the present study with the majority being females (72.5%) and Chinese (79.7%). Cronbach's alpha analysis suggested removing three Likert-scale items, with the remaining 13 items being accepted. Generally, no significant difference was noted between the two groups (p = 0.197), but three items were found to be significant (p < 0.05), with higher mean scores in the feedback sandwich group. Moreover, no significant difference was noted between the two feedback models (p = 0.325) when controlling gender and ethnicity. The open-ended question showed that students in the feedback sandwich group expressed greater positive perceptions. Conclusion Although students generally had positive perceptions of both feedback models, they tended to favour the feedback sandwich. Neither gender nor ethnicity affected the students' perceptions of the two feedback models.